Modulation of pathogenic oral biofilms towards health with nisin probiotic. Issue 1 (1st January 2020) - Radaic, Allan; Ye, Changchang; Parks, Brett; Gao, Li; Kuraji, Ryutaro; Malone, Erin; Kamarajan, Pachiyappan; Zhan, Ling; Kapila, Yvonne L.
ABSTRACT: Background: Oral dysbiosis is an imbalance in the oral microbiome and is associated with a variety of oral and systemic diseases, including periodontal disease, caries, and head and neck/oral cancer. Although antibiotics can be used to control this dysbiosis, they can lead to adverse side effects and superinfections. Thus, novel strategies have been proposed to address these shortcomings. One strategy is the use of probiotics as antimicrobial agents, since they are considered safe for humans and the environment. Specifically, the Gram-positive Lactococcus lactis, a species present in the oral and gut microbiota, is able to produce nisin, which has been used worldwide for food preservation. Objective: The objective of this study was to test whether a nisin probiotic can promote a healthier oral microbiome in pathogen-spiked oral biofilms. Results: We found that L. lactis can prevent oral biofilm formation and disrupt 24-h and 48-h pre-formed biofilms. Finally, we demonstrate that both treatments, a nisin-producing L. lactis probiotic and nisin can decrease the levels of pathogens in the biofilms and return the diversity levels back to control or 'healthy' levels. Conclusion: A nisin-producing probiotic, can be used to treat 'disease-altered' biofilms and promote healthier oral biofilms, which may be useful for improving patient oral health.